Determinants of first-year students’ career path in Ghana - Akumbuno, Alexander; Mensah, Grace; Amankwa, Joy Seko Abra; Akuna, Elliot; Owusu-Sekyere, Francis; Kissi-Abrokwah, Bernard (Technium Social Sciences Journal, 2025)
A successful career chosen by the student is the essential component in academic success. The aim of this study was to examine the determinants of first-year students’ career paths in Ghana. The study was underpinned by Trait and Factor Theory (TFT), Social Cognitive Career Theory (SCCT), the Theory of Reasoned Action (TRA), and the theory of planned behaviour (TPB). The study was based on interpretive philosophical assumptions, and a qualitative approach was used to investigate the factors that influence the choice of career path of first-year university students in Ghana. All in all, 36 students were purposefully selected in three focus groups. The study found that socioeconomic, educational, sociocultural, and individual factors were the key determinants of a student’s career path. The study concluded that students from wealthy backgrounds have greater flexibility in choosing career paths that align with their interests than those from lower-income backgrounds. Again, it was revealed that students’ personal values and desires have a positive impact on their career paths.